2013
DOI: 10.18172/cig.1034
|View full text |Cite
|
Sign up to set email alerts
|

Factores en la generación de crecidas en una cuenca de campos abandonados, Pirineo central español

Abstract: Factors explaining the temporal variability of peak flows in an experimental catchment of the Central Pyrenees have been studied. This catchment (Arnás, Borau Valley) was cultivated until 50 years ago and is now abandoned; it is characterized by a quick hydrological response against any intensity and volume of precipitation. The total volume of precipitation during each rainfall event hardly explains the intensity of peak flows, which show a high variability. Relationships between precipitation and discharge v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Despite the wide range of discharge and sediment transport parameters, the clockwise shaped events had a clear recognisable hysteretical behaviour, and hydrographs and sedigraphs can be described as typical (see Arnáez et al, 1999, García-Ruiz et al, 2000.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the wide range of discharge and sediment transport parameters, the clockwise shaped events had a clear recognisable hysteretical behaviour, and hydrographs and sedigraphs can be described as typical (see Arnáez et al, 1999, García-Ruiz et al, 2000.…”
Section: Resultsmentioning
confidence: 99%
“…However, only the maximum rainfall intensity of the storm is significantly correlated with the amount of stormflow discharge on / or? the total discharge (Arnáez et al, 1999). The discharge is normally free of suspended sediment and has a low conductivity (around 340 µS cm -1 at 25ºC), which is considerably lower during flood events.…”
Section: The Study Areamentioning
confidence: 99%
“…The maximum suspended sediment concentration was about 15 g l À1 , as estimated using an ISCO automatic sampler because the turbidimeter reach saturation for suspended sediment concentration above 5.5 g l À1 . The average solute concentration was 250 mg l À1 during floods and 350 mg l À1 during baseflow discharge (Arnáez et al, 1999).…”
Section: Sediment Transportmentioning
confidence: 99%
“…For the above reasons, the number of experimental catchments has increased markedly in recent years (Walling, 1991), particularly in Spain, where they are found in contrasting environments ranging from areas with a semiarid Mediterranean climate (Castillo et al, 2000;Cantón et al, 2004), to high Pyrenean mountains (Alvera and García-Ruiz, 2000), mid-altitude mountains (Gallart et al, , 2002Llorens et al, 1997;Arnáez et al, 1999;García-Ruiz et al, 2000Serrano-Muela et al, 2008), and dehesa environments (Ceballos and Schnabel, 1998).…”
mentioning
confidence: 99%
“…These authors reported that the proportion of bedload transported at the event scale varied between 10% and 30% of the total sediment. The continuous measurement of conductivity together with the samples collected by the water sampler enabled ARNÁEZ et al (1999) to estimate an average solute concentration of 250 mg l -1 during floods and 350 mg l -1 during base flow discharge.…”
Section: Estimation Of An Annual Sediment Balancementioning
confidence: 99%